2008
DOI: 10.1017/s0952523808080310
|View full text |Cite
|
Sign up to set email alerts
|

Transporter-mediated GABA responses in horizontal and bipolar cells of zebrafish retina

Abstract: GABA-mediated interactions between horizontal cells (HCs) and bipolar cells (BCs) transform signals within the image-processing circuitry of distal retina. To further understand this process we have studied the GABA-driven membrane responses from isolated retinal neurons. Papaindissociated retinal cells from adult zebrafish were exposed to GABAergic ligands while transmembrane potentials were monitored with a fluorescent voltage-sensitive dye (oxonol, DiBaC 4 (5)). In HCs hyperpolarizing, ionotropic GABA respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
(127 reference statements)
0
10
0
Order By: Relevance
“…, 1985; Ayoub & Lam, 1987; O’Malley & Masland, 1989; Connaughton et al. , 2008; Nelson et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…, 1985; Ayoub & Lam, 1987; O’Malley & Masland, 1989; Connaughton et al. , 2008; Nelson et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The termination of the synaptic action of GABA is achieved by its uptake into presynaptic neuronal terminals and into the surrounding glial cell processes. In addition to neurons such as amacrine and interplexiform cells (Moran et al, 1986; Pow et al, 1996) and, in the fish retina, horizontal and bipolar cells (Nelson et al, 2008), Müller cells and, at least under pathological conditions, astrocytes and microglia take up GABA (Sarthy, 1982; Osborne et al, 1995). It was suggested that in the retinas of most lower vertebrates and birds, GABA removal is almost exclusively mediated by neurons, whereas in the mammalian retina, neurons, and Müller cells remove extracellular GABA (Yazulla, 1986; but, see below).…”
Section: Gaba Uptake and Metabolismmentioning
confidence: 99%
“…Though GABA hyperpolarized most bipolar cells, a minority of isolated cells (∼5%) were depolarized by GABA (Nelson et al, 2008). GABA-elicited depolarizations were only observed in OFF-bipolar cells (unpublished observations).…”
Section: Bipolar Cell Types Their Physiological Properties and Recementioning
confidence: 99%